TELAAH HUKUM TA’ADDUD JUMU’AH YANG DILAKUKAN OLEH PONDOK PESANTREN AL-ISLAM JORESAN MLARAK PONOROGO - Dini Arifah Nihayati (An-natiq Jurnal Kajian Islam Interdisipliner, 2022)
The law of ta'addud jumuah becomes a question as the number of Muslims increases. Imam Syafi'i as a scholar whose fatwa is adopted by the majority of Muslims in Indonesia has stated that it is forbidden to do ta'adud jumu'ah. but in fact, the modern era demands ta'addud jumu'ah. Previous research on legal issues related to Friday prayers is still focused on community traditions in Friday prayers, services to congregational Friday prayers, and has not touched the law of implementing ta'addud jumu'ah. For this reason, the author uses a masail fiqhiyah approach. Masail fiqhiyyah is the study of solving new problems in the lives of Muslims and using the ijtihad method to solve them.. This study concludes that the ta'adud jumu'ah conducted by the Al-Islam Islamic Boarding School is classified as permissible where the Al-Islam Dormitory mosque is not too close to the Jami' mosque in Joresan village so that there is no possibility of disturbing each other and not damaging the harmony of the people. Islam in the village of Joresan. This research is expected to provide answers regarding the law of ta'addud jumu'ah which will be very much needed in the midst of the growing number of Muslims.